2012
DOI: 10.1186/1471-2180-12-160
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic concentrations of antibiotics inhibit Shiga toxin release from enterohemorrhagic E. coli O104:H4 from the 2011 German outbreak

Abstract: BackgroundThe shiga toxin-producing E. coli (STEC) O104:H4 caused a major outbreak in Germany in spring 2011. STEC are usually susceptible to common antibiotics. However, antibiotic treatment of STEC-infected patients is not recommended because STEC may enhance production and release of shiga toxins (STX) in response to antibiotics, which eventually enhances the frequency and severity of clinical symptoms, including haemolytic uraemic syndrome (HUS) and fatalities.ResultsWe characterized the response to antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…Moreover, the study showed a similar effect of rifampicin at the sub-MIC level on the stx2 transcription levels and Stx2 release. In addition, it indicated similar results when compared to our study when E. coli O104:H4 was subjected to the MIC and the sub-MIC of gentamicin (Corogeanu et al, 2012). Similar results with gentamicin at the sub-MIC level in one strain of E. coli O104:H4 were observed in another study done by Bielaszewska et al; however, these results were insignificant (Bielaszewska et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the study showed a similar effect of rifampicin at the sub-MIC level on the stx2 transcription levels and Stx2 release. In addition, it indicated similar results when compared to our study when E. coli O104:H4 was subjected to the MIC and the sub-MIC of gentamicin (Corogeanu et al, 2012). Similar results with gentamicin at the sub-MIC level in one strain of E. coli O104:H4 were observed in another study done by Bielaszewska et al; however, these results were insignificant (Bielaszewska et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The effects of some antibiotics were strongly dependent on their concentrations, causing either an increase or decrease in efficiency of Shiga toxin production (44)(45)(46). In this light, it is important to note that it was reported recently that STEC strain O104:H4, which caused a recent outbreak in Germany, did not release Shiga toxin in response to therapeutic concentrations of ciprofloxacin, meropenem, fosfomycin, and chloramphenicol (47). Definitely, different classes of antibiotics differentially influence Shiga toxin production (48), and effects of particular antibiotics are dependent on their concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] However, recent reports during a German outbreak established new evidence regarding antibiotic usage. [18][19][20] In conclusion, Acinetobacter infection should be considered as a plausible cause of typical HUS in cases with no E. coli infection. The high frequency and degree of adaptability and transformability among some strains of Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%